2017
DOI: 10.1109/tnsre.2017.2664801
|View full text |Cite
|
Sign up to set email alerts
|

A Wearable Hip Assist Robot Can Improve Gait Function and Cardiopulmonary Metabolic Efficiency in Elderly Adults

Abstract: The aims of this paper were to investigate the effectiveness of a newly developed wearable hip assist robot, that uses an active assist algorithm to improve gait function, muscle effort, and cardiopulmonary metabolic efficiency in elderly adults. Thirty elderly adults (15 males/ 15 females) participated in thispaper. The experimental protocol consisted of overground gait at comfortable speed under three different conditions: free gait without robot assistance, robot-assisted gait with zero torque (RAG-Z), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 47 publications
0
58
0
Order By: Relevance
“…Seventeen publications presented improved human walking and/or running economy using an exoskeleton versus without using a device during preferred levelground conditions: twelve exoskeletons improved walking economy [11][12][13][25][26][27][28][29][30][31][32][33], four improved running economy [14,15,17,18], and one improved both walking and running economy [16] versus using no device ( Fig. 2).…”
Section: Exoskeleton User Performance: Insights and Trendsmentioning
confidence: 99%
“…Seventeen publications presented improved human walking and/or running economy using an exoskeleton versus without using a device during preferred levelground conditions: twelve exoskeletons improved walking economy [11][12][13][25][26][27][28][29][30][31][32][33], four improved running economy [14,15,17,18], and one improved both walking and running economy [16] versus using no device ( Fig. 2).…”
Section: Exoskeleton User Performance: Insights and Trendsmentioning
confidence: 99%
“…Several exoskeleton prototypes are being developed to assist people with mobility impairments including older adults. Age-related changes in gait function (e.g., decreased walking speed, shorter step length, increased step variability, and reduced range of motion at the hip, knee, and ankle joints) and decreased metabolic efficiency for walking strongly affect the ability to perform daily activities [13,31]. Improving walking function is therefore an important focus when developing exoskeletons for older adults.…”
Section: Advances In the Development Of Exoskeleton Technologymentioning
confidence: 99%
“…Improving walking function is therefore an important focus when developing exoskeletons for older adults. Lab studies with older adults showed that the Gait Enhancing Mechatronic System (GEMS)-a wearable hip exoskeleton that provides walking assistance-can improve gait function and cardiopulmonary metabolic efficiency and reduce muscle effort [13,14]. In other work, seven older adult men walked on a treadmill at a constant speed for 50 minutes both with and without wearing a robotic hip exoskeleton called the Stride Assistance System (SAS) [31].…”
Section: Advances In the Development Of Exoskeleton Technologymentioning
confidence: 99%
“…The Gait Enhancing and Motivating System-Hip (GEMS-H), developed by Samsung Electronics Co., Ltd. (Suwon, Republic of Korea), is a hip-type robotic exoskeleton. Our previous studies showed that GEMS-H improved gait function, muscle efficiency, and cardiopulmonary metabolic efficiency [7][8][9][10]. However, it is not yet known how GEMS-H assisted gait training modulates cortical activity of stroke patients.…”
Section: Introductionmentioning
confidence: 98%